A decolonizing ear : documentary film disrupts the archive - Landry, Olivia (University of Toronto Press, 2023)
"The recording of Indigenous voices is one of the most well-known methods of colonial ethnography. In A Decolonizing Ear, Olivia Landry offers a skeptical account of listening as a highly mediated and extractive act, influenced by technology and ideology. Returning to early ethnographic practices of voice recording and archiving at the turn of the twentieth century, with a particular focus on the German paradigm, she reveals the entanglement of listening in the logic of Euro-American empire and the ways in which contemporary films can destabilize the history of colonial sound reproduction. Landry provides close readings of several disparate documentary films from the late 1990s and the early 2000s. The book pays attention to technology and knowledge production to examine how these films employ recordings plucked from different colonial sound archives and disrupt their purposes. Drawing on film and documentary studies, sound studies, German studies, archival studies, postcolonial studies, and media history, A Decolonizing Ear develops a method of decolonizing listening from the insights provided by the films themselves."--